Implementasi Pendekatan Konseling oleh Guru BK dalam Mengatasi Kenakalan Siswa (Studi pada Siswa SMP Nurul Burhan) - Ayu Rahmawati; Nurjannah (Jurnal Pendidikan Sosial Dan Konseling, 2024)
Delinquency in early adolescent students often occurs, this is a transition from childhood to adulthood.This research contains how the role of a counselor as a problem solver in overcoming delinquency in students. This research uses descriptive qualitative methodology with the aim of knowing what approaches and techniques or treatments the counselor has applied in overcoming delinquency in Nurul Burhan Junior High School students. This research uses pupossive sampling technique, namely sampling by determining certain objectives and criteria. in this study there were four teachers and 3 students. This research shows that the approach applied is a humanistic and behavioristic approach, the treatment given by the counselor is using the punishment method, individual counseling, and classical guidance.